Ash cenosphere formation, fragmentation and its contribution to particulate matter emission during solid fuels combustion - Li, Yi (Curtin University, 2012)
Electricity generated from stationary coal-fired power stations has been playing an important role in powering the global economy and is projected to continue its key role in the foreseeable future. However, substantial quantities of fly ash are produced from coal-fired power stations as solid wastes every year, not only exerting significant pressure on waste management but also having adversely impacts on environment. Therefore, there has been considerable R&D to develop technologies for minimizing these adverse impacts of fly ash via various routes e.g. fly ash utilisation.Ash cenospheres are light-weight, thin-walled and hollow ash particles as part of the fly ash produced from solid fuels combustion. These light-weight ash particles are considered to be valuable materials for manufacturing various value-added products. Since almost half a century ago, substantial R&D was conducted to characterize ash cenospheres and understand their formation mechanisms during the combustion of pulverised solid fuels e.g. coal. Unfortunately, the fundamental mechanisms responsible for ash cenosphere formation during pulverized solid fuels combustion are still largely unclear.Therefore, the research program in this PhD study aims to carry out a systematic investigation on ash cenosphere formation, fragmentation behaviour and its contribution to ash and particulate matter formation during solid fuels combustion. The specific objectives are to 1) investigate the possible formation mechanisms of ash cenospheres via characterizing the properties of ash cenospheres collected from a coal-fired power station; 2) reveal the fundamental formation mechanism of ash cenospheres during solid fuels combustion using pyrite as a model fuel; and 3) demonstrate the phenomenon of ash cenosphere fragmentation during solid fuel combustion and provide direct experimental evidence on its role in ash and particulate matter formation during solid fuels combustion.To accomplish these objectives, ash cenosphere samples were collected from a coal-fired power station. A systematic experimental program was also designed and conducted in a DTF system under various conditions using pyrite as a model fuel. The ash cenosphere samples and ash samples collected from laboratory experiments (including ashes collected in the cyclone and PM10 collected by a DLPT) were characterized by various analytical methods. The specific objectives have been successfully achieved in this PhD study.Firstly, the characterization of narrow size-fractioned ash cenospheres collected from a coal-fired power station indicates that SiO2/Al2O3 ratio decreases with the increase of ash cenosphere size, accompanied with an increase in the sum of TiO2 and Fe2O3 contents. The gas products locked inside various ash cenosphere size fractions are dominantly CO2 and some N2. The average gas pressure decreases from 0.227 atm to 0.172 atm (NTP) as particle size increases from 63−75 μm to 150−250 μm. Thermomechanical analysis further shows that ash cenospheres of different size fractions do not melt at 1600 °C, suggesting that these ash cenospheres from coal-fired power station are impossible to be formed at temperatures < 1600 °C.Ash chemistry of individual cenospheres indicates that the optimum particle temperature for cenosphere formation is ~1640 – 1800 °C. Under these conditions, molten ash droplets can be formed and grow by trapping a certain amount of gas generated within the ash droplets. The growth of cenosphere precursors is governed by the wide range of viscosity of molten cenosphere precursors together with the force of surface tension, which is demonstrated to be inversely proportional to the viscosity of molten droplets, producing ash cenospheres with various wall thicknesses. The data also appear to suggest that apart form Fe2O3, TiO2 may play a role in the formation of ash cenospheres during pulverized coal combustion.Secondly, a systematic experimental program was designed to fundamentally investigate the formation mechanism of ash cenosphere during solid fuels combustion in a drop-tube furnace (gas temperature: 530 – 1100 C; residence time: 1.1 s) using pulverized pyrite (38-45 μm) as a model fuel. The results show that the formation of ash cenosphere commences at a furnace temperature as low as 580 °C. At furnace temperatures 600 C, ash products of pyrite combustion consist of dominantly large ash cenospheres (up to 130 μm in diameter) with thin shells (1−3 μm) and ash cenosphere fragments of various sizes. An increase in furnace temperature leads to enhanced ash cenosphere fragmentation. The presence of O2 is found to be essential to the formation of molten Fe-S-O droplets. The sulphur oxides gaseous products produced within the droplets inflate to form cenospheric precursors, followed by further oxidation and resolidification transforms these cenospheric Fe-S-O precursors into final ash cenospheres that also experience fragmentation and contain dominantly iron oxides.Thirdly, a set of experiments were also carried out to combust pulverised pyrite at 600 C in the drop-tube furnace system but at various residence times (0.4, 0.7, 0.9 and 1.1 s). Substantial amounts of PM10 (dominantly PM1-10 and also some PM1) are produced during the combustion of pulverised pyrite. The PSDs of PM10 have a bimodal distribution, i.e. a fine mode with a mode diameter of 0.26 μm and a coarse mode with mode diameters from 4.4 μm to 6.8 μm. At 0.4 s residence time, the production of ash cenospheres is limited. As the residence time increases, the formation of complete ash cenospheres and their fragments increases substantially, suggesting the enhanced fragmentation of ash cenospheres. As a result, there is a substantial increase in the yield of PM10 at a longer residence time (e.g. 1.1 s). Therefore, the results in this study provide direct experimental evidences to demonstrate the important role of ash cenosphere fragmentation in PM10 formation.Overall, the present study provides original and new insights into the formation mechanism of ash cenospheres during solid fuels combustion using pulverized pyrite as a model fuel. As the first time in the field, it clarifies the role of ash cenosphere fragmentation and its significant contribution to particulate matter emission. The characteristics of ash cenospheres of various size fractions also provide essential insights into ash cenosphere formation during pulverized coal combustion. Most importantly, the research methodology taken in this PhD study, particularly the design of the systematic experimental program using pyrite as a model fuel provides a simple (but not simpler) solid fuel combustion system for investigating complicated thermochemical process of ash cenosphere formation. This approach makes it possible to thoroughly understand the fundamental formation mechanism of ash cenosphere during solid fuels combustion.